Eskimo graves from Upernavik District. - Hjarnø, Jan; Fennow, Karin (Meddelelser om Grønland, 1974)
In connection with the National Museum's archaeological investigations in Upernavik District in the summer of 1967 (Hjarnø, J., 1968) a large number of Eskimo burials were uncovered for the purpose of collecting usable skeletal materials for anthropological investigations. A total of 52 graves was investigated; as indicated below, these graves were distributed numerically on the following islands: 32 Angmaussaq*) 5 Upernaviarssuk, 8 Sãtoq, 2 Tapeq, 1 Nunâ and 4 Nordø. (For the situation of the localities see fig. 1). Graves are an extremely common occurrence in the area. Most frequently they consist of a chamber built of stone containing the remains of the corpse or corpses. A domed heap of stones covers the chamber's exterior. The graves are usually situated on dry, rocky slopes, ledges, and the like, but in a few cases the graves lie in swampy terrain. The graves near the Nûgârssuk settlement on Angmaussaq can be mentioned as an example of the latter (HJARNØ, J., 1968) The opening of the graves took place according to a rather standard pattern: as soon as a grave was observed it was photographed, and its location and height a. s. l. were recorded on a sketch map. The area around the stone heap was next examined for the purpose of finding possible grave goods. The burial chamber was then uncovered, photographed, and measured. Suitable crania and thigh bones, as well as possible grave goods, were removed, marked, and packed in plastic bags. Data and a description of the entire operation were recorded in a notebook; finally the grave was restored and marked with a painted number. Upon return to Copenhagen the archaeological specimens were deposited in the National Museum and the skeletal remains in the University's Anthropological Laboratory. *) (The name is unauthorized, according to files).